Coronary CT angiography in calcified coronary plaques: Comparison of diagnostic accuracy between bifurcation angle measurement and coronary lumen assessment for diagnosing significant coronary stenosis. - Sun, Zhonghua; Xu, L.; Fan, Z. (2015)
BACKGROUND: To investigate the diagnostic value of coronary CT angiography (CCTA) by bifurcation angle measurement in the assessment of calcified plaques compared to conventional coronary lumen analysis. METHODS: Fifty-three patients with calcified plaques identified on CCTA in the left coronary artery were included in the study. Minimal lumen diameter (MLD) and bifurcation angle between the left anterior descending (LAD) and left circumflex (LCx) arteries were measured and compared between CCTA and invasive coronary angiography (ICA), while the areas under the curves (AUCs) by receiver-operating characteristic curve analysis (ROC) were compared between CCTA and ICA with regard to the diagnostic value of using bifurcation angle as a criterion. RESULTS: On a per-vessel assessment, the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) and 95% confidence interval (CI) with the use of bifurcation angle for determining coronary stenosis were 100% (86%, 100%), 79% (59%, 92%), 81% (62%, 92%), and 100% (85%, 100%) for CCTA, and 100% (86%, 100%), 82% (63%, 94%), 83% (65%, 94%), and 100% (85%, 100%) for ICA, respectively. While the sensitivity and NPV remained unchanged, the specificity and PPV of CCTA by MLD were 33% (21%, 47%) and 43% (31%, 56%). The AUCs by ROC curve analysis for CCTA and ICA bifurcation angle measurements demonstrated no significant difference (p>0.05, 0.79 vs 0.86, and 0.70 vs 0.68 at the LAD and LCx assessment, respectively). CONCLUSION: Coronary CT angiography by bifurcation angle measurement shows significant improvement in the diagnosis of calcified plaques with diagnostic value comparable to invasive coronary angiography.